Cleft lip and palate malformations: Essential knowledge for the general practitioner - M.G.C. Giaquinto-Cilliers; M.D. Potgieter; D.A. Links; G.I. van Schalkwyk (South African Family Practice)
Cleft lip and palate malformations are a common group of congenital abnormalities, and are therefore frequently encountered by the general practitioner, who is often the primary coordinator in the management of these patients. This is especially true in a South African setting, where specialist treatment is not always readily available. An incomplete understanding of the multiple components and complexities of the condition often results in unsatisfactory patient outcomes. This article aims to improve understanding of the condition and demonstrates how a multidisciplinary team approach is essential to successfully manage these patients. The roles of the different team members are described, and include the dentist, orthodontist, paediatrician, geneticist, speech therapist, dietitian, otorhinolaryngologist, as well as plastic and reconstructive and/or maxillofacial surgeon. A flow diagram with the various role players and the timing of their interventions has been designed to simplify the referral pathway. The authors aim to assist the general practitioner with the appropriate referral of patients with cleft lip and palate.